IMPLEMENTASI PERMA NO. 01 TAHUN 2016 DALAM PROSES MEDIASI PERKARA PERCERAIAN DI PENGADILAN AGAMA PADANGSIDIMPUAN - Dermina Dalimunthe; Zulfan Efendi Hasibuan (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2024)
This study aims to find out (1) the mediation process at the Padangsidimpuan Religious Court after the issuance of PERMA No. 1 of 2016 (2) Inhibiting and supporting factors for mediators in carrying out mediation at the Padangsidimpuan Religious Court. (3) The effectiveness of mediation after the implementation of PERMA No. 1 of 2016 at the Padangsidimpuan Religious Court. This research uses a qualitative descriptive approach. The subjects of this study were judges, mediators, clerks, junior clerks, and employees at the Padangsidimpuan Religious Court. Data collection techniques in this study are interviews, observation and documentation. The results of the study show that (1) the Padangsidimpuan Religious Court has carried out the mediation process in accordance with PERMA No. 01 of 2016 concerning mediation procedures in court and making the PERMA a reference in applying mediation. (2) The success factor of mediation from the aspects of the parties and the mediator, before carrying out the mediation process, he first studies the problems that cause cases faced by both parties. Factors inhibiting the implementation of PERMA No. 01 of 2016 at the Padangsidimpuan Religious Court, namely: the duration of the mediation time, the large number of divorce cases making the judge concurrently a mediator judge, non-judge mediators from outside the court who only number two people so it is very limited. (3) PERMA No. 01 of 2016 has not been effective because the percentage of cases that were withdrawn (successfully mediated) did not arrive, this was due to inadequate law enforcement elements. If seen from the theory of legal effectiveness, both from the legal factor PERMA No. 01 of 2016, law enforcement factors (mediators), infrastructure factors, community factors and cultural factors at the Padangsidimpuan Religious Court have not been effective.